2013
DOI: 10.1371/journal.pone.0056385
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Zygotes Respond to Severe Sperm DNA Damage by Delaying Paternal DNA Replication and Embryonic Development

Abstract: Mouse zygotes do not activate apoptosis in response to DNA damage. We previously reported a unique form of inducible sperm DNA damage termed sperm chromatin fragmentation (SCF). SCF mirrors some aspects of somatic cell apoptosis in that the DNA degradation is mediated by reversible double strand breaks caused by topoisomerase 2B (TOP2B) followed by irreversible DNA degradation by a nuclease(s). Here, we created zygotes using spermatozoa induced to undergo SCF (SCF zygotes) and tested how they responded to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 56 publications
9
109
0
2
Order By: Relevance
“…As demonstrated in a variety of vertebrates, unrepaired DNA lesions from paternal origin promote a slower paternal DNA replication (Gawecka et al 2013), de novo mutations propagated to the next generation, such as hereditary diseases (Carroll & Marangos 2013), chromosomal structural aberrations (Marchetti et al 2015) and even lead to arrest in embryo development (Gawecka et al 2013). As has been demonstrated in human and mouse, zygotic DNA repair initially depends on the oocyte-born mRNAs and proteins and, additionally, on genes expressed very early in development (Derijck et al 2008, Jaroudi et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in a variety of vertebrates, unrepaired DNA lesions from paternal origin promote a slower paternal DNA replication (Gawecka et al 2013), de novo mutations propagated to the next generation, such as hereditary diseases (Carroll & Marangos 2013), chromosomal structural aberrations (Marchetti et al 2015) and even lead to arrest in embryo development (Gawecka et al 2013). As has been demonstrated in human and mouse, zygotic DNA repair initially depends on the oocyte-born mRNAs and proteins and, additionally, on genes expressed very early in development (Derijck et al 2008, Jaroudi et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fertilization with DNA-damaged sperm increases the risk of promoting pregnancy loss in mammals (Speyer et al 2010), arrest in embryo development or embryo death (Perez-Cerezales et al 2010b, Gawecka et al 2013, birth defects, chromosomal abnormalities and other genetic diseases (Fernandez-Gonzalez et al 2008, Barroso et al 2009, Schulte et al 2010, Marchetti et al 2015. The DNA-repairing activity relies on the oocyte machinery once the fertilization takes place (Aitken et al 2014, Fernandez-Diez et al 2015, the zygote being responsible for repairing the sperm damage.…”
Section: Introductionmentioning
confidence: 99%
“…During fertilization events, the early embryo undergoes substantial remodeling of the paternal and maternal derived genetic and epigenetic information (73) to establish a totipotent embryo; therefore, any changes or alterations, as a result of an environmental insult, during these key developmental time frames could permanently alter phenotypes in offspring. As replication and pronuclear repair of both the paternal and maternal genomes after fertilization relies solely on maternal derived machinery and mitochondrial derived substrates (27), alterations to sperm chromatin state from paternal obesity coupled with impaired mitochondrial quality from maternal obesity may result in a further delay in genome activation. This could trigger downstream consequences of further impaired cell allocations and embryo development, transcriptional changes in the blastocyst and subsequent placenta, which in turn affect fetal growth, altering the growth trajectory of offspring and increasing susceptibility to adult chronic disease (45).…”
Section: Combined Effect On Fetal Growth From Maternal and Paternal Omentioning
confidence: 99%
“…The same has been confirmed in the study conducted by Ashwood-Smith and Edwards [15]. The time needed for DNA repair affects the rate of embryo development which has been proved in the experiments on murine embryos carried out by Gawecka et al [18]. The authors induced the damage of genetic material used for ICSI and found that the duration of initial stages of embryo development increased with the intensity of induced damage.…”
Section: Discussionmentioning
confidence: 56%
“…The significance of embryo development rate has also been confirmed in the study conducted by Campbell et al who found longer times to reach subsequent developmental stages in the presence of genetic anomalies during real-time monitoring of human embryo growth [19]. The studies carried out by Gawecka et al and Campbell et al emphasize the initial rate of embryo development is vital for the embryo selection for transfer, even when this seems to have no effect on ICSI efficiency [18,19]. A considerably slower rate of embryo development and less successful pregnancy achievement in older women as demonstrated in our study may be explained using the results obtained by Grøndahl et al [4].…”
Section: Discussionmentioning
confidence: 83%